PENDIDIKAN SEKSUAL PADA ANAK SD SEBAGAI UPAYA MENURUNKAN KEJAHATAN SEKSUAL DI LINGKUNGAN SEKITAR - Neng Hanifiah Neng Hanifiah Radhia Robbi; Nana Hendracipta; Siti Rokmanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
In the current era of digitalization, many elementary school children do not make good use of technology. Thus the role of teachers is important in managing children's behavior to prevent acts of sexual violence that will occur in their environment. In this case, a qualitative research method is used to compare the opinions of other journals, then reviewed in this discussion. By providing education to students, it can prevent and reduce sexual harassment. Sex education in children is very important to prevent violence and sexual deviations in children. Sex education in children needs to be implemented gradually and in accordance with the age and level of development of the child. It can be concluded that sex education plays an important role in efforts to reduce the level of sexual harassment and crime, because by providing socialization related to sex education to elementary school students, children will be more understanding and mentally healthy.